Frequency and Demographic Correlates of Post-Stroke Dementia in A Tertiary Care Hospital: Frequency and Demographic Correlates of Post-Stroke Dementia - Khan, Shahbaz; Arshad, Waleed; Nizamani, Samahir Akram; Bughio, Abdul Hafeez; Seelro, Sajid Hussain; Kashif, Amber (Pakistan Journal of Health Sciences, 2025)
Post-stroke dementia (PSD) is a significant yet under-recognized complication following cerebrovascular events, contributing to long-term disability and reduced quality of life. Objectives: To determine the frequency and demographic correlates of PSD among stroke survivors admitted at Liaquat University Hospital, Jamshoro. Methods: This prospective cohort study was conducted in the Department of Neurology, Liaquat University of Medical and Health Sciences (LUMHS), Jamshoro. A total of 143 ischemic stroke patients aged 55–90 years were enrolled using non-probability consecutive sampling. Patients with confounding neurological or psychiatric conditions were excluded. Dementia was assessed six months after stroke onset using the Mini-Mental State Examination (MMSE), with a score <24 indicating post-stroke dementia (PSD). Results: The mean age was 69.25 ± 10.11 years. Of the participants, 51.7% were male, 67.8% were urban residents, and 55.9% were unemployed. PSD was observed in 22.4% of patients. Although slightly higher frequencies of PSD were noted among older, urban, and unemployed individuals, none of the demographic factors, including age, gender, employment, residence, education, or family history of dementia, were significantly associated with PSD (p>0.05 for all). Conclusions: Post-stroke dementia affects a substantial proportion of stroke survivors. Despite the lack of statistically significant demographic correlates, the observed burden warrants routine cognitive assessment and post-stroke rehabilitation strategies, particularly in tertiary care centers in Pakistan.